Investigation of Safety Culture among Young Workers - Kiani, Moien; Behm, Michael (East Carolina University, 2019)
According to the Occupational Safety and Health Administration (OSHA), young workers whose ages range from 14 to 24 and are interested in finding different jobs during the summer or during the school year are considered at great risk of occupational injuries and accidents. This is due to their lack of experience and the nature of their developmental stages in different aspects such as emotion, cognition and physical features. Notably, the number of workers under the age of 24 is considerable and thus, the safety and health of these workers will be important. For instance, in 2016, NIOSH reported that approximately 19.3 million workers were under the age of 24 in the United States and represented 13% of the workforce. The vulnerability of such workers could also be due to a lower level of maturity, work related safety and health training, skills, perception of safety and occupational risks, and typically higher level of work speed and work load compared to the older workers. This could be the reason they are at high risk of work related injuries and diseases. The International Labor Organization (ILO) considers one of the possible factors that could generally create risk inequality among workers is organizational culture; Safety culture is a particular part of organizational culture considering shared beliefs, values and attitudes in organizations that could be a contributory factor in safe operations. Purpose of Study/Participants/Research Method Three important points should be considered in safety among youth workers 1. Informing young workers about their rights 2. Reducing their lack of knowledge regarding safety 3. Reducing their hesitation in talking about safety issues at work. Moreover, there is an importance regarding some safety culture factors in the study of young workers because such factors exert considerable influence on young workers safety and health at work. By reason of this, four safety culture factors were selected as follows: management commitment, safety involvement, safety communication, and work environment. The purpose of this research is to survey students within the College of Engineering and Technology at East Carolina University who are currently working or have previously worked during the summer. The descriptive analytical survey-based research utilizing the descriptive statistics and the statistical tests (SPSS Software) will be applied to observe how safety culture factors correlate with each other in the study of young workers, how safety culture and its structural factors correlate with demographic variable, and to evaluate how youth workers perceive safety culture and its structural factors.
Keywords: Safety Culture; Industrial safety--United States; Young adults--Employment--United States; Safety education, Industrial--United States